1998
DOI: 10.3109/10428199809092688
|View full text |Cite
|
Sign up to set email alerts
|

PreB1 (CD10-) Acute Lymphoblastic Leukemia: Immunophenotypic and Genomic Characteristics, Clinical Features and Outcome in 38 Adults and 26 Children

Abstract: The less differentiated stage (CD10-) of B-lineage acute lymphoblastic leukaemia (ALL) described as preB1-ALL in the GEIL nomenclature, accounts for less than 10% of ALL. It is classically considered to be associated with translocation (4;11)(q21;q23), and to have a poor prognosis. We report an extensive immunophenotypic, genomic and clinical study of a series of 64 preB-1 ALL patients, representing 6.3% of a cohort of consecutive ALLs. The engagement of preB1-ALL cells in the B-lineage was confirmed by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In our study, the frequency of pro-B-ALL cases, calculated within the entire ALL population, was 16%. This incidence is slightly superior to the percentage reported in other recent studies on adult ALL, 13,25,26 but it is close to the percentage 13.4% reported in a previous GIMEMA study carried out in 304 adult patients with ALL immunophenotyped in 43 Italian centers between 1988 and 1991. 27 Within B-lineage ALL, the prevalence of pro-B-ALL was 21.4%.…”
Section: Discussionsupporting
confidence: 69%
“…In our study, the frequency of pro-B-ALL cases, calculated within the entire ALL population, was 16%. This incidence is slightly superior to the percentage reported in other recent studies on adult ALL, 13,25,26 but it is close to the percentage 13.4% reported in a previous GIMEMA study carried out in 304 adult patients with ALL immunophenotyped in 43 Italian centers between 1988 and 1991. 27 Within B-lineage ALL, the prevalence of pro-B-ALL was 21.4%.…”
Section: Discussionsupporting
confidence: 69%
“…Prior studies have confirmed the correlation between lack of CD10 expression in ALL with aberrant CD15 and CD65 expression and MLL rearrangements in both adults and infants. [17][18][19][20] Other similarities between infant pro-B ALL and therapy-related leukemia have also been described. Cimino et al 21 analyzed the specific breakpoints in the MLL gene in infant leukemias, de novo leukemias and topoisomerase II inhibitor-related leukemias, and found similarities in gene breakpoints between the infant and therapy-related group that was not found in the de novo leukemia group.…”
Section: Discussionmentioning
confidence: 99%
“…Immunological markers B-I (pro-B) ALL No further B-cell differentiation marker (only HLA-DR, TdT, CD34) B-II (common) ALL As above, plus CD10 B-III (pre-B) ALL As B-I/B-II, plus cytoplasmic IgM B-IV (mature) ALL Cytoplasmic/surface kappa or lambda Among other markers, stages B-I and B-II are often CD24 positive and 4G7 (pro-and pre-B surrogate light chain specific MoAb) positive [25,26]; surface CD20 and CD22 are variably positive beyond stage B-I; CD13 and CD33 myeloid/cross lineage antigen can be expressed, as well as the CD34 stem-cell antigen, particularly in Ph + ALL (often B-II with CD34, CD38, CD25 and CD13/33) [27,28], but myeloid-specific CD117 should not be present and can be used to differentiate further between ALL and rare myeloid leukemias with negative myeloperoxidase expression (see Section 2.2) [29]. Pro-B ALL with t(4;11)/MLL rearrangements is most often myeloid antigen-positive disease (including expression of CD15).…”
Section: Categorymentioning
confidence: 96%